2019
DOI: 10.1111/clr.13518
|View full text |Cite
|
Sign up to set email alerts
|

Early loading of splinted implants in posterior mandible: Three‐year results of a prospective multicenter study

Abstract: Objective: To evaluate the clinical outcomes of an early loading protocol of splinted implants with a fluoride-modified nanostructure surface and a tapered apex design for the therapy of posterior partial edentulism of mandible. Materials and Methods:One hundred and seven implants were placed in the mandible of 45 subjects at three centres in China. A minimum of two and a maximum of three implants were placed in an edentulous region using a one-stage protocol.Each subject received a screw-retained, splinted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
2
0
3
Order By: Relevance
“…Single, partial and complete prosthetic constructions were included. Radiographic data from 14 prospective, multicentre clinical trials with a 3‐ to 5‐year follow‐up were retrieved from a database (Dentsply Sirona Implants, Mölndal, Sweden) (Ban et al., 2015; Cooper et al., 2014, 2019; Galindo‐Moreno et al., 2017; Han et al., 2018; Liu et al., 2019; Sanz et al., 2014; Schliephake et al., 2012; Stanford et al., 2016; Temmerman et al., 2019; Thoma et al., 2018; Toljanic et al., 2016; Xie et al., 2015; Zadeh et al., 2018). The aforementioned studies were approved by the Local Ethical Committee at each study centre (Supplement).…”
Section: Methodsmentioning
confidence: 99%
“…Single, partial and complete prosthetic constructions were included. Radiographic data from 14 prospective, multicentre clinical trials with a 3‐ to 5‐year follow‐up were retrieved from a database (Dentsply Sirona Implants, Mölndal, Sweden) (Ban et al., 2015; Cooper et al., 2014, 2019; Galindo‐Moreno et al., 2017; Han et al., 2018; Liu et al., 2019; Sanz et al., 2014; Schliephake et al., 2012; Stanford et al., 2016; Temmerman et al., 2019; Thoma et al., 2018; Toljanic et al., 2016; Xie et al., 2015; Zadeh et al., 2018). The aforementioned studies were approved by the Local Ethical Committee at each study centre (Supplement).…”
Section: Methodsmentioning
confidence: 99%
“…According to the authors, the response of the cortical bone to the applied stress consisted of the rearrangement of its structure and an increase in its mass [ 13 ]. On the other hand, Liu et al placed 107 implants in 45 patients and observed a statistically significant bone gain 12, 24 and 36 months after loading [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…El 64,1% de los implantes fué insertado en el sector posterior y el 35,9% en el sector anterior. El sector posterior representa el área ideal para valorar el éxito biomecánico de los implantes porque son sometidos a mayores fuerzas masticatorias y las cargas oclusales y parafuncionales se concentran más en esta región [33][34] .…”
Section: Discusionunclassified
“…Los protocolos de carga precoz se han desarrollado, fundamentalmente, porque ha mejorado el conocimiento de la oseointegración que ha ayudado a desarrollar nuevos diseños de los implantes modernos. Las espiras cervicales y la superficie arenada y/o grabada) han logrado incrementar un buen contacto hueso-implante y una rápida oseointegración 9,[17][18][19] . También se han desarrollado nuevos materiales y aditamentos protésicos así como mayores niveles de precisión y ajuste que han logrado una mejor unión pilar-implante, y han reducido también el tiempo de espera de la carga funcional convencional a protocolos de carga precoz con unos resultados funcionales y estéticos muy favorables [43][44] .…”
Section: Discusionunclassified
See 1 more Smart Citation